Labor Markets in Latin America: A Supply-Side Story - Suzanne Duryea; Miguel Székely (Inter-American Development Bank, Office of the Chief Economist, 1998)
This paper shows that the factors affecting labor supply have been key determinants of the changes in employment, unemployment, and income differentials in Latin America in the 1990s. The two main forces driving labor supply in the region have been demographics and education.
Keywords: 330; Arbeitsmarkt; Bevölkerungsentwicklung; Bildungsniveau; Arbeitsangebot; Erwerbstätigkeit; Lateinamerika